SEVERAL TACTICAL AND LEGAL ASPECTS OF PRELIMINARY MEASURES OF SEARCHING MISSING PERSONS - Makans, Leonīds (Administrative and Criminal Justice, 2018)
The article deals with the problems of searching missing persons and inviolability of private life of a person, namely, how proportionate, and reasonable is the publication of sensitive data of a person in the mass media when disappearance of a person reported. Analysis of the statistical indicators of the searching of missing persons gives basis for the conclusion that a significant number (80%) of persons reported as missed, in fact they are not such, but without warning their relatives were absent for various reasons – somewhere stayed late, left their place of residence for other reasons, went abroad. Nevertheless, photographs and other sensitive data of such persons are published in the mass media. Moreover, there was an opinion on the need to bring to administrative responsibility those who left the place of residence without warning their relatives. On the author’s opinion, one of the reasons for the unjustified use of the media for searching for persons and violating the privacy of a person is the poor performance of the preliminary searching measures for clarify the circumstances and causes of disappearance. The article also proposes to amend the definition of the missing person, clarify the essence of the notion of “to declare a search”, the procedure and officials authorized to declare such a search, and also introduce the category “Persons who have lost contact with relatives”.